Elastic strain engineering of ferroic oxides. (12th February 2014) - Schlom, Darrell G.; Chen, Long-Qing; Fennie, Craig J.; Gopalan, Venkatraman; Muller, David A.; Pan, Xiaoqing; Ramesh, Ramamoorthy; Uecker, Reinhard
Abstract